Insights to Preventive Dentistry via Salivary Defensin Peptide: Evaluating B-Defensins for Caries Control and Periodontal Disease Prevention :A Systematic Review and Meta-Analysis - Manzar Anwar Khan; Muhammad Mustafa; Mehwish Munawar; Ashar Hussain; Muhammad Amin Sahito; Khurram Anwar; Fatima Ali (Pakistan Journal of Medicine and Dentistry, 2025)
Background: Salivary β-defensins form an essential part of oral immune system activity since they lead microbial balance control and help prevent dental caries and periodontal diseases. This systematic review and meta-analysis examine the role of salivary β-defensins in preventive dentistry by evaluating their association with dental caries incidence and their potential contribution to periodontal disease prevention.